2021
DOI: 10.1093/ckj/sfab208
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolic risk factors and outcomes of patients with kidney transplant nephrolithiasis

Abstract: Background Nephrolithiasis in allograft kidneys is rare but this diagnosis may lead to allograft complications and patient morbidity. Previous studies that have evaluated nephrolithiasis post-transplant focused on surgical stone management with limited data on urine metabolic risk factors and presence of stones after follow-up. Methods We retrospectively evaluated kidney transplant recipients who were diagnosed with transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…Urinary tract stones in transplant patients may be associated with foreign bodies (suture material at the ureteroneocystostomy site), recurrent infections or due to metabolic changes in the post-transplant kidney 2. A small number of allograft kidney stones are due to pre-existing stones in the donor kidney 3 4. Of the de novo stones formed, about one-third of the recipients are found to be stone formers prior to the transplant 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary tract stones in transplant patients may be associated with foreign bodies (suture material at the ureteroneocystostomy site), recurrent infections or due to metabolic changes in the post-transplant kidney 2. A small number of allograft kidney stones are due to pre-existing stones in the donor kidney 3 4. Of the de novo stones formed, about one-third of the recipients are found to be stone formers prior to the transplant 3.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of allograft kidney stones are due to pre-existing stones in the donor kidney 3 4. Of the de novo stones formed, about one-third of the recipients are found to be stone formers prior to the transplant 3. De novo stones can occur 1 month to many years after kidney transplantation 1–3…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors can lower urine citrate excretion by causing hyperkalemia and impairing ammonium production, leading to excretion of acidic urine or even overt metabolic acidosis. 20,21 Mycophenolate mofetil may also cause hypocitraturia by inducing diarrhea, resulting in bicarbonate loss from the stool and metabolic acidosis. 20,21 The ensuing metabolic acidosis in these patients will further lower urine citrate excretion or urine pH, both significant risk factors for calcium and uric acid stones.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Mycophenolate mofetil may also cause hypocitraturia by inducing diarrhea, resulting in bicarbonate loss from the stool and metabolic acidosis. 20,21 The ensuing metabolic acidosis in these patients will further lower urine citrate excretion or urine pH, both significant risk factors for calcium and uric acid stones. 20,22 Although we did not find an association between the use of calcineurin inhibitors or mycophenolate mofetil and kidney stone events, it is possible that longer follow-up time is needed to detect potential effects of maintenance immunosuppression on stone recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary oxalosis is also associated with an increased risk of stone formation in the kidney allograft. In a retrospective study, Bolen et al [23] evaluated kidney transplant recipients diagnosed with transplant nephrolithiasis. The study showed that in patients with nephrolithiasis, 94% of the patients had urine citrate of <450 mg excreted in 24 h, along with 61% of the patients with a urine oxalate execration of !30 mg in 24 h. As expected, CaOx composition was the most common.…”
Section: Oxalate Nephropathy and Its Impact On Kidney Allograft Outcomesmentioning
confidence: 99%